ANALISIS DINAMIKA KELOMPOK SENTRA PENYULUHAN KEHUTANAN DAN PEDESAAN MANGGA DELIMA TAMAN NASIONAL KARIMUNJAWA - Diarsi Eka Yani; Idha Faridha (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2017)
Comprehensive development is a management process combined with the socio-economic aspects of the community, especially in the buffer zone of the National Park area. The community can play a role in extension activities through Forestry and Rural Extension Center (SPKP) in order to encourage productivity’s enhancement and community’s autonomy through various productive activities undertaken. The research objectives are (1) identify individual characteristics, and (2) analyze the dynamics of SPKP Mangga Delima Karimunjawa National Park group. The research used census method in SPKP Mangga Delima, Kemujan village, Karimunjawa distrcts. The research used census method in SPKP Mangga Delima, Kemujan village, Karimunjawa districts. There were 16 respondents that are members of the group. Data analysis used frequency distribution and description. The findings of individual characteristic are mostly (56,25%) middle adult age (36-50 years old), formal education less than 9 years (62,50%), less good cosmopolitan (56,25%) participate in decision making (87,50%), and join member less than 5 years (62,50%). The findings for the dynamics of the group are most respondents consider the group objectives are good enough (50%) and good (50%), the group structure is good enough (56.25%), the group task function is good (81.25%), the coaching and group development is good enough (81.25%), the group cohesiveness is good (62.5%), the group atmosphere is good (56.25%), the group tension is good enough (50%) and good (50%), the group effectiveness is good enough (50%).